Diagnostic Criteria Of Henoch–Schönlein Purpura (Hemorrhagic Vasculitis) In Children (Texas Journal of Medical Science, 2025)
Henoch–Schönlein purpura (IgA vasculitis) is the most common systemic vasculitis of childhood. Despite the availability of international diagnostic standards, clinical heterogeneity and atypical presentations continue to contribute to delayed or inaccurate diagnosis, increasing the risk of renal and gastrointestinal complications. The EULAR/PRINTO/PRES criteria remain the most widely adopted framework, but their practical effectiveness requires continuous evaluation in light of new clinical and immunopathological evidence